The role of microglial autophagy in Parkinson’s disease - Zhu, Rui; Luo, Yuyi; Li, Shangang; Wang, Zhengbo (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is the second most common neurodegenerative disease. Studies have shown that abnormal accumulation of α-synuclein (α-Syn) in the substantia nigra is a specific pathological characteristic of PD. Abnormal accumulation of α-Syn in PD induces the activation of microglia. Microglia, which are immune cells in the central nervous system, are involved in the function and regulation of inflammation in PD by autophagy. The role of microglial autophagy in the pathophysiology of PD has become a hot-pot issue. This review outlines the pathways of microglial autophagy, and explores the key factor of microglial autophagy in the mechanism of PD and the possibility of microglial autophagy as a potential therapeutic target for PD.